Video for Travel - an effective solution for applying video in the tourism domain - Miranda, N.; Raminhos, R.; Pereira, H.; Trigo, V. (International Journal of Innovations in Business, 2013)
Video for Travel is a web platform that exploits the video format richness in the promotion and communication of tourism offers while integrated in OTA (Online Travel Agency) business web portals. The usage of video as a fundamental part of any tourism business management solution is applied three ways: (i) offer promotion close to potential customers using a rich, interactive and involving format, (ii) non-supervision / automatic video creation based on business data and promotion definitions, minimizing costs and improving efficiency as well as (iii) purchase support through video chat that creates a new channel for customer interaction with cross-selling and up-selling opportunities. Further, a video-learning open platform was also created specialized in tourism content (i.e. academic, business and technical) made available to students and tourism professionals, representing a single and specialized knowledge repository for the tourism domain. The platform is mainly focused on professionals and businesses in the tourism sector, both OTA companies that sell tourism products online as well as companies / individuals that are responsible for the actual tourism product implementation / execution that require new and more engaging ways of reaching their potential customers, providing a product preexperience even before its purchase. Video for Travel is a R&D project supported by the QREN programme, developed by Viatecla (technological background) and ISCTE (communication and marketing background). Upon its conclusion in 2012 the project is currently in a pilot phase for one major Portuguese OTA company. This paper presents the project in its more technological approach, describing the concept, design, architecture and implementation effort.